[Bundanon and the Bundanon Trust : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Bundanon is a large home near Nowra, New South Wales, Australia, which was the home of the painter Arthur Boyd, and is listed on the Register of the National Estate. Bundanon was donated to the people of Australia in 1993 by Arthur and Yvonne Boyd, who believed "you can't own a landscape" and wanted to share the place that inspired them with everyone, along with the adjoining property which was owned by the Artist Sidney Nolan. The Australian Government established Bundanon Trust as a wholly owned Australian Government company limited by guarantee, with the Company holding the gift as a charitable trust. The Trust's Board of Directors reports directly to the Minister for the Environment, Heritage and the Arts, who in turn appoints the Chairperson and the Directors. Bundanon is now open to the public, and contains an educational centre, and constantly evolving studio space for artists and writers. There are currently four studios with attached residences and a writers cottage which are offered meritoriously to a select group of talented individuals from all over the world.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Boyd, Arthur, -- 1920-1999; Bundanon Trust; Art, Australia -- Exhibitions; Poetry -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Bundanon House (Bundanon, N.S.W.)